Construction of a survival nomogram for gastric cancer based on the cancer genome atlas of m6A-related genes - Wang, Xiaokang; Xu, Kexin; Liao, Xueyi; Rao, Jiaoyu; Huang, Kaiyuan; Gao, Jianlin; Xu, Gengrui; Wang, Dengchuan (Frontiers in Genetics, 2022)
Objective: Based on the TCGA database, a prediction model for 1-, 3- and 5-year overall survival rates of gastric cancer (GC) patients was constructed by analyzing the critical risk factors affecting the prognosis of gastric cancer patients. Method: Clinicopathological features as well as gene signature of GC patients were obtained from the TCGA database. Patients were randomly divided into a training cohort and an internal validation cohort. Independent predictors of GC prognosis were analyzed by univariate and multivariate cox analysis to construct nomogram. The accuracy and reliability of the model was further validated by calibration curves, ROC curves and C-indexes, and the clinical utility of the model was analyzed by decision analysis curves. Result: Age, sex, N stage, M stage, METTL16, RBM15, FMR1, IGFBP1 and FTO were significantly associated with the prognosis of GC patients and these predictors were further included in the construction of nomogram. The C-indexes for the training cohort and validation set were 0.735 and 0.688, respectively. The results of the ROC curve analysis indicated that the area under the curve (AUC) exceeded 0.6 in training and validation sets at 1, 3 and 5 years. Conclusion: We have constructed and validated a nomogram that provides individual survival condition prediction for GC patients. The prognostic model integrating gene signatures and clinicopathological characteristics would help clinicians determine the prognosis of patients with GC and develop individualized treatment plans.